2016
DOI: 10.1037/dev0000130
|View full text |Cite
|
Sign up to set email alerts
|

Productive extension of semantic memory in school-aged children: Relations with reading comprehension and deployment of cognitive resources.

Abstract: We investigated 7- to 10-year-old children’s productive extension of semantic memory through self-generation of new factual knowledge derived through integration of separate yet related facts learned through instruction or through reading. In Experiment 1, an experimenter read the to-be-integrated facts. Children successfully learned and integrated the information and used it to further extend their semantic knowledge, as evidenced by high levels of correct responses in open-ended and forced-choice testing. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…On the other hand, in cases in which knowledge extension is contingent on single-trial learning procedures, such as in the present research, integrative encoding is necessary but not sufficient for explicit knowledge extension. Consistent with this notion, in a child analogue of the paradigm employed here, Varga and Bauer (2013) inserted delays throughout the learning process and found that self-derivation through integration consisted of a two-step process, one of integrative encoding followed by flexible manipulation of that information at test (see Bauer, Blue, Xu, & Esposito, 2016 for similar encoding results using eye-tracking). It is therefore reasonable to suggest that related stem facts may be integrated in advance of a test probe which then further prompts explicit self-derivation.…”
Section: Discussionsupporting
confidence: 64%
“…On the other hand, in cases in which knowledge extension is contingent on single-trial learning procedures, such as in the present research, integrative encoding is necessary but not sufficient for explicit knowledge extension. Consistent with this notion, in a child analogue of the paradigm employed here, Varga and Bauer (2013) inserted delays throughout the learning process and found that self-derivation through integration consisted of a two-step process, one of integrative encoding followed by flexible manipulation of that information at test (see Bauer, Blue, Xu, & Esposito, 2016 for similar encoding results using eye-tracking). It is therefore reasonable to suggest that related stem facts may be integrated in advance of a test probe which then further prompts explicit self-derivation.…”
Section: Discussionsupporting
confidence: 64%
“…In Bauer, Blue, Xu, and Esposito (2016), self-generation of new factual knowledge through integration of separate episodes of new learning was evidenced in a paradigm in which children were required to integrate across separate sentences conveying true but novel facts. Self-generation was related to reading comprehension as tested using the Woodcock Johnson Test of reading comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…As such, individual variability in the process of self-generation through integration can be expected to relate to academic achievement. Indirect evidence consistent with this prediction comes from laboratory tests with 7- to 10-year-olds (Bauer, Blue, Xu, & Esposito, 2016). Children either read or were read facts by an experimenter in the process of a board game.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…In future research, it would be beneficial to develop alternative paradigms that permit administration of a larger number of test trials. Steps in this direction were taken in Bauer, Blue, Xu, and Esposito (), in which 7‐ to 10‐year‐old children played a board “game” during which they learned a number of novel stem facts. They later were tested on up to 10 trials of self‐generation based on integration of the stem facts.…”
Section: Discussionmentioning
confidence: 99%